THE ECOLOGICAL MANAGEMENT CONSULTANCY AND ENVIROMENTAL PROTECTION - Mihailović, Branko; Paraušić, Vesna; Hamović, Vladana (Economics of Agriculture, 2007)
The way of doing business in domestic firms has been based on the nonmarket principles for a long time. It has created growing imbalance between domestic and market economy. The competition and business success have motivated the firms in Serbia to apply the principles of market economy. Consultancy is one of the most important factors of effective location of company resources and improving business practice. As learnning and development model of managers abilities and skills enables solving problems of businees and improving business performance of company. New investion methods of decision making require establishing relation between criteria location of economics, socials and ecologicals factors. Consultancy that respects situation approach in practice can gain balance of economic efficiency, social responsible work and organic production standards.